Komunistyczny aparat bezpieczeństwa w Polsce wobec mniejszości białoruskiej w kraju i Białorusinów antykomunistów na Zachodzie (w latach czterdziestych, pięćdziesiątych i sześćdziesiątych) - Grzybowski, Jerzy (Pamięć i Sprawiedliwość, 2011)
A group of people of Belarusian origin who used to collaborate with the Third Reich during World War II settled down in postwar Poland. From the very beginning, due to their anti-Communist past, they were under the watchful eye of the Bezpieka (Department of Public Security, Resort Bezpieczeństwa Publicznego and later Ministry of Public Security, Ministerstwo Bezpieczeństwa Publicznego). According to the definition derived from the security apparatus’ dictionary, that category of Polish citizens was the so-called „Belarusian burgeois nationalists”.During the 1940s and 1950s „nationalists’” circles were under constant Bezpieka’s control. Those who belonged to the Belarusian anti-Communist political emigration in the West were taken a close interest in of the Security apparatus’ services. Polish citizens of Belarusian origin were being exploited in the process of uncovering activists of Belarusian opposition in the West. In order to haven them being kept under active surveillance inside and outside the country, Polish security apparatus worked in collaboration with the Soviet one.